Analisa Produktivitas Produksi Gula di PG. Gempolkrep dengan Metode Omax dan RCA (Rootcause Analysis) - Santoso, Krisna Agung; Pupanantasari Putri, Erni (SURYA TEKNIKA, 2024)
Productivity is the spearhead of a company's survival, if there is an increase in productivity it shows the company's success in carrying out the production process. P.G. Gempolkrep Mojokerto is a sugar factory located in Gempolkrep Village, Gedeg District, Mojokerto Regency. The research aims to measure and analyze the causes of decreased productivity based on 3 criteria, namely Raw Materials, Labor, Machine Hours, Electrical Energy and Sugarcane Yield. The method in this research uses the Objective Matrix Method (OMAX) with stages of Determining Criteria (Defining), Measuring Criteria (Quantifying) and Productivity Index Analysis (Monitoring). On 1 - 15 August 2023, productivity was the best with a productivity index of 1,000, while the lowest productivity occurred on 16 - 31 May 2023, amounting to 30.30. On 16 - 31 July 2023, the overall productivity level was the best with a change index to standard productivity of 192%. Meanwhile, the worst Overall Productivity occurred on 1 - 15 September 2023, amounting to - 45.4%.